Dark archives : a librarian's investigation into the science and history of books bound in human skin - Rosenbloom, Megan, 1981- (New York : Farrar, Straus and Giroux, 2020)
"A medical librarian presents a fascinating, terrifying look into history's rarest books-- those bound in human skin-- and the stories of their creation and collection"--
The First Printing -- This Dreadful Workshop -- Gentlemen Collectors -- Skin Craft -- Secrets of the Sages-Femmes -- The Long Shadow of the Night Doctors -- The Postmortem Travels of William Corder -- Echoes of Tanner's Close -- The Highwayman's Gift -- Ghosts in the Library -- My Corpse, My Choice -- The French Connection -- Epilogue: Humane Anatomy -- The Anthropodermic Book Project's List of Confirmed Human Skin Books as of March 2020.
Includes bibliographical references and index.
PB
Keywords: Anthropodermic books